2014
DOI: 10.1007/s12253-014-9742-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between SNPs Within Antioxidant Genes and the Risk of Prostate Cancer in the Siberian Region of Russia

Abstract: In the present study we investigated the association of a number of polymorphic changes in antioxidant system genes (SNPs rs1050450 in the GPX1 gene, rs1695 and rs1138272 in the GSTP1 gene and rs4880 in the MnSOD gene) with the risk of prostate cancer. The association of disease stage and PSA levels with specific genotypes was also analyzed. A study was conducted with the participation of 736 Russian men. We compared the frequency of occurrence of the studied alleles in patients with prostate cancer (392) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Overall, 88 studies with 33,098 cases and 37,831 controls were included in this meta-analysis. Of the 88 studies, 24 studies focused on breast cancer [ 9 11 , 16 , 38 , 60 , 61 , 68 , 69 , 71 , 72 , 77 , 88 , 93 , 96 , 97 , 100 , 105 , 109 , 114 , 119 , 122 , 127 ]; 17 on prostate cancer [ 37 , 66 , 74 , 79 , 82 , 85 , 86 , 89 , 95 , 106 , 111 , 113 , 120 , 125 , 128 ]; six for each of the following cancer types, such as lung cancer [ 7 , 17 , 18 , 65 , 92 , 118 ], bladder cancer [ 8 , 15 , 67 , 75 , 112 , 117 ], and pancreatic cancer [ 64 , 91 , 102 , 107 , 108 , 121 ]; five on colorectal cancer [ 13 , 63 , 73 , 94 , 101 ]; three for each of the following cancer types, such as ovarian cancer [ 70 , 81 , 87 ], hepatocellular carcinoma [ 98 , 99 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 88 studies with 33,098 cases and 37,831 controls were included in this meta-analysis. Of the 88 studies, 24 studies focused on breast cancer [ 9 11 , 16 , 38 , 60 , 61 , 68 , 69 , 71 , 72 , 77 , 88 , 93 , 96 , 97 , 100 , 105 , 109 , 114 , 119 , 122 , 127 ]; 17 on prostate cancer [ 37 , 66 , 74 , 79 , 82 , 85 , 86 , 89 , 95 , 106 , 111 , 113 , 120 , 125 , 128 ]; six for each of the following cancer types, such as lung cancer [ 7 , 17 , 18 , 65 , 92 , 118 ], bladder cancer [ 8 , 15 , 67 , 75 , 112 , 117 ], and pancreatic cancer [ 64 , 91 , 102 , 107 , 108 , 121 ]; five on colorectal cancer [ 13 , 63 , 73 , 94 , 101 ]; three for each of the following cancer types, such as ovarian cancer [ 70 , 81 , 87 ], hepatocellular carcinoma [ 98 , 99 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been demonstrated that a T-to-C substitution in the SOD2 gene could result in a valine (Val) to alanine (Ala) amino acid change, thus causing higher MnSOD enzymatic activity. Moreover, a growing number of studies have discovered a connection between the MnSOD Val16Ala polymorphism (rs4880) and the risk of PCa (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Therefore, this single-nucleotide polymorphism might play an important role in prostate carcinogenesis.…”
mentioning
confidence: 99%
“…An additional 56 articles were excluded, including 56 articles with unavailable data on the genotype frequency of CC, CT, and TT within GSTP1 rs1138272, and 4 articles in which the data were not in HWE. After a quality evaluation, 40 articles (Harris et al, 1998; Saarikoski et al, 1998; Park et al, 1999; Wadelius et al, 1999; Welfare et al, 1999; Marshall et al, 2000; Stanulla et al, 2000; Krajinovic et al, 2002; Wang et al, 2003, 2011; Sorensen et al, 2004; Yang et al, 2004; Garcia-Closas et al, 2005; Landi et al, 2005, 2007; Moore et al, 2005; De Roos et al, 2006; Lira et al, 2006; Marciniak et al, 2006; Jiao et al, 2007; Li et al, 2007, 2010; Murphy et al, 2007; Al-Dayel et al, 2008; Kury et al, 2008; Siraj et al, 2008; Van Emburgh et al, 2008; Zienolddiny et al, 2008; Canova et al, 2009; Northwood et al, 2010; Sainz et al, 2011; Ebrahimkhani et al, 2012; Garcia-Gonzalez et al, 2012; Ibarrola-Villava et al, 2012; Dura et al, 2013; Oskina et al, 2014; Ghatak et al, 2016; De Mattia et al, 2017; Minina et al, 2017; Rajesh et al, 2018) of good quality were included. Finally, we included a total of 43 case-control studies for our quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…We removed one case-control study in which the data were not in HWE (Marie-Genica Consortium on Genetic Susceptibility for Menopausal Hormone Therapy Related Breast Cancer Risk, 2010), and we removed two additional studies (Barnette et al, 2004) because they failed to meet the requirement of reporting the genotype frequency in both the case and control group. Moreover, 17 new articles (Park et al, 1999; Welfare et al, 1999; Marshall et al, 2000; Stanulla et al, 2000; Krajinovic et al, 2002; De Roos et al, 2006; Lira et al, 2006; Li et al, 2007, 2010; Sainz et al, 2011; Garcia-Gonzalez et al, 2012; Dura et al, 2013; Oskina et al, 2014; Ghatak et al, 2016; De Mattia et al, 2017; Minina et al, 2017; Rajesh et al, 2018) were added. Finally, a total of 40 articles were included in our updated meta-analysis.…”
Section: Discussionmentioning
confidence: 99%